1983
DOI: 10.1139/o83-013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liver plasma membranes on G-actin. I. Possible implication of membrane NPases in inactivation of G-actin

Abstract: G-actin incubated in the presence of a liver fraction enriched in plasma membranes is rapidly inactivated, as indicated by the biphasic loss of polymerizability and DNase inhibition. The rates of inactivation as measured by viscosity are greatly influenced by temperature, but almost independent of membrane concentrations at least in the low range of concentrations tested (less than 250 micrograms protein/ml). The loss of DNase inhibition capacity proceeds at rates two to three times slower than the loss of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We have found that the effects of 5'-nucleotidase on actin inhibition ofdeoxyribonuclease are due to contaminating ATPases, which has also been shown for chick gizzard 5'-nucleotidase . The ability of actin to inhibit deoxyribonucleotidase I is lost on incubation at 37°C in the absence of ATP (results not shown), an effect that appears to be speeded up by the presence ofATPases (Gruda et al, 1983) and to be related to loss ofactin-bound nucleotide . The interaction with F-actin proposed for this chick gizzard 5'-nucleotidase, associated with enzyme inhibition, does not occur with pure rat liver 5'-nucleotidase.…”
Section: Discussionmentioning
confidence: 91%
“…We have found that the effects of 5'-nucleotidase on actin inhibition ofdeoxyribonuclease are due to contaminating ATPases, which has also been shown for chick gizzard 5'-nucleotidase . The ability of actin to inhibit deoxyribonucleotidase I is lost on incubation at 37°C in the absence of ATP (results not shown), an effect that appears to be speeded up by the presence ofATPases (Gruda et al, 1983) and to be related to loss ofactin-bound nucleotide . The interaction with F-actin proposed for this chick gizzard 5'-nucleotidase, associated with enzyme inhibition, does not occur with pure rat liver 5'-nucleotidase.…”
Section: Discussionmentioning
confidence: 91%
“…G-actin was prepared from acetone powder of rabbit skeletal muscles and a plasma-membrane-enriched preparation from rabbit liver as described elsewhere (1).…”
Section: Matenids and Methodsmentioning
confidence: 99%